Implementation of the Tpack-Based Project Based Learning (Pjbl) Learning Model to Increase Students' Learning Motivation in Class XI History Subjects SMAN 1 Gunungsari - Taufik Hidayat; Rosada (Institute of Educational, Research, and Community Service, 2024)
The objectives of this study are as follows: 1) To assess the learning motivation of students before the implementation of the